Triglyceride to high density lipoprotein cholesterol ratio and major adverse cardiovascular events in ACS patients undergoing PCI - Shangxun Zhou; Miaohan Qiu; Kexin Wang; Jing Li; Yi Li; Yaling Han (Scientific Reports)
Abstract The triglyceride to high density lipoprotein cholesterol (TG/HDL-C) ratio has been consistently linked with the risk of coronary heart disease (CHD). Nevertheless, there is a paucity of studies focusing on acute coronary syndrome (ACS) patients undergoing percutaneous coronary intervention (PCI) or experiencing bleeding events. The study encompassed 17,643 ACS participants who underwent PCI. Survival analysis, Cox regression analysis and restricted cubic spline (RCS) were employed to assess the associations between TG/HDL-C ratio and the risk of major adverse cardiovascular events (MACE), all-cause death, cardiac death and all-cause bleeding events. Over a 12-month follow-up period, 638 (3.9%) patients experienced MACE while 2837 (16.1%) patients experienced bleeding events. The TG/HDL-C ratio exhibited significant positive correlations with the incidence of MACE, all-cause death and cardiac death; conversely it displayed significant negative correlations with the incidence of all-cause bleeding. Patients in the high quartile TG/HDL-C category demonstrated significantly higher risks for MACE compared to those in the low quartile category, with hazard ratio (HR) [95%confidence interval (CI)] of 1.46 (1.17–1.83); conversely, they showed significantly lower risks for all-cause bleeding compared to their counterparts in the low quartile group, with HR (95%CI) of 0.72 (0.65–0.81). The structure of subgroup analyses remained robust and consistent, with gender being the sole factor interacting with TG/HDL-C specifically in relation to MACE events (P for interaction = 0.037). A higher baseline TG/HDL-C ratio was associated with an elevated risk of MACE but a reduced risk of bleeding events in ACS patients undergoing PCI.